Performance of the New BioMonitor 2‐AF Insertable Cardiac Monitoring System: Can Better be Worse?. Issue 5 (23rd March 2017) - LACOUR, PHILIPP; DANG, PHI LONG; HUEMER, MARTIN; PARWANI, ABDUL SHOKOR; ATTANASIO, PHILIPP; PIESKE, BURKERT; BOLDT, LEIF‐HENDRIK; HAVERKAMP, WILHELM; BLASCHKE, FLORIAN
Abstract : Background: Implantable loop recorders (ILR) are valuable tools for the investigation of patients with suspected arrhythmias. The BioMonitor 2‐AF is a novel insertable ILR with enhanced atrial fibrillation (AF) detection algorithm and remote monitoring capability. Objective: The objective of this first‐in‐human study with the BioMonitor 2‐AF was to analyze course of P‐wave sensing performance and R‐wave amplitude, prevalence of false and correctly sensed and classified episodes, and effectiveness of remote monitoring. Methods: All 19 patients who underwent ILR insertion were included in the BIOTRONIK Home Monitoring® system (BIOTRONIK GmbH, Berlin, Germany). Daily changes in P‐wave and R‐wave sensing were analyzed over 6 weeks. A breathing test (in‐ and expiration) was performed in two different body positions at baseline and during a 6‐week in‐house follow‐up to investigate alterations of P‐wave and R‐wave sensing. Results: R‐wave amplitude and the high P‐wave visibility (94.4%) remained unchanged during the follow‐up period. In most patients both an increase and decrease of R‐wave amplitude, and in some cases a complete R‐wave vector change (31.6%), was documented during the "breathing test." Change of body position did not alter R‐wave sensing amplitude mostly. "Breathing test" and change of body position had no effect on P‐wave sensing performance. In 15.8% of the patients, misclassification of episodes as AF or high ventricular rates due to P‐wave oversensing occurred. No ILR‐related complication occurred. Automatic transmission via BIOTRONIK Home Monitoring® was successful 100% of the time. Conclusion: This study demonstrates that the BioMonitor 2‐AF is a safe and effective tool for continuous cardiac monitoring.